Fakultas Ekonomi dan Ilmu Sosial Universitas Islam Negeri Sultan Syarif Kasim Riau - Ikhwani Ratna (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Political and career officials have a different character but is a unity in the government who should be able to synergize with each other. However, in line with the reform of the bureaucracy, the politicization of the bureaucracy have made a messy political position in the pattern of relationships and careers in the bureaucracy. This study sought to answer the question how to reform the bureaucracy to the relationship between political officials and career officials in the Environment Government of Riau Province, any problems that exist / arise, and how to organize the pattern of the relationship between political and career positions in the bureaucracy that occurred in Riau Provincial Government Environment.